Metagenomics reveals functional species and microbial mechanisms of an enriched thiosulfate-driven denitratation consortia. (December 2021) - Liu, Yihui; Wang, Yingmu; Fan, Gongduan; Su, Xiaoxuan; Zhou, Jian; Liu, Deming
Highlights: Average NAE of TDD system reached 82.24 ± 17.09% under S/N molar ratio of 1.00. After S2 O3 2- was depleted, the formed S 0 preferred the reduction of NO2 – than NO3 – . Microbial mechanisms of TDD were investigated by metagenomics for the first time. Enrichment of T . sp. 65–29 and washout of Nir -related species led to high NAE. Quorum sensing regulation might be crucial for denitratation consortia enrichment. Abstract: In this study, thiosulfate-driven denitratation (TDD) system was successfully established under optimal S/N molar ratio of 1.00, with nitrite accumulation efficiency (NAE) of 82.24 ± 17.09%. This work highlighted that thiosulfate significantly preferred the reduction of nitrate than nitrite. However, after the depletion of thiosulfate, the in-situ formed intermediate product element sulfur (S 0 ) served as the main electron donor, and significantly favored the reduction of nitrite than nitrate, which constrained nitrite accumulation and nitrate removal. In addition, metagenomic sequencing revealed that the functional denitratation species might be Thiobacillus _sp._65-29, but the occurrence of Nir -annotated species would decrease nitrite accumulation. Under S/N ratio of 1.00, the decreased abundant Nir -annotated species (e.g., Thiobacillus _sp.), as well as the down-regulated quorum sensing interactions between Nar - and Nir -annotated species were key microbial metabolisms of high NAE in the TDD system. Overall, this work provides new sight into the metagenome-base functional species and metabolic potential of thiosulfate-driven denitratation.